Assessment of Variability in Physicochemical Water Parameters of Lake Nyabihoko, Western Uganda. - Abraham, Atuhaire (Kabale University, 2024)
The study assessed the spatial and seasonal variabilities in the physicochemical water quality parameters of Lake Nyabihoko. In determining the physicochemical quality of Lake Nyabihoko, fifty-four (54) water samples were collected from nine sampling stations for six months and analyzed. Water temperature, dissolved oxygen (DO), turbidity, electrical conductivity (EC), Total Dissolved Solids (TDS), and pH were measured in the field. Parameters such as total alkalinity, hardness, magnesium, calcium, potassium, phosphate, and chloride were determined in the laboratory following APHA (2017) standard guidelines for physicochemical analysis. Analysis of variance showed that the mean values for all the measured physicochemical parameters did not differ significantly (p > 0.05) among the sampling stations except for magnesium. The mean values for the measured parameters of DO, EC, turbidity, TDS, chloride, and phosphates significantly differed between sampling seasons except for temperature, pH, hardness, alkalinity, calcium, magnesium, and nitrates. The lake’s Water Quality Index (WQI) values ranged from 82.9 to 88.8, with an overall mean value of 86.1, which belongs to the “very poor” class of drinking water quality based on the WQI classification. Seasonally, WQI varied, with the wet season having a higher WQI value (81.0) than the dry season (76.8). All the measured parameters fell within the permissible Uganda National Bureau of Standards (UNBS) and World Health Organisation (WHO) standard ranges except for turbidity, magnesium, and phosphates. The study recommends a community catchment management plan with proper monitoring to mitigate the deterioration of the water quality and sustain the public health and livelihood around the lake.